Evaluation of lifestyle in women with breast cancer referred to Imam Sajad hospital, Ramsar in 2015 - Keihanian, Shahrbanoo; Fallah Ghadi, Somayeh; Zakerihamidi, Maryam; Saravi, Ali; Saravi, Shadi; Saravi, Mohammad Mansoor (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: Cancer is a devastating chronic disease that affects all aspects of life. Lifestyle is an important factor which is related with higher incidence of breast cancer, and it can be modified by education. Investigation of the role of lifestyle on the incidence of cancer in women needs special attention. This study aimed to assess the lifestyle in women with breast cancer. Materials and Methods: This was a descriptive study. The sample was 60 patients admitted in oncology ward of Imam Sajad Hospital, Ramsar for chemotherapy in 2015. Lifestyle in patients assessed by lifestyles questionnaire (LSQ). Data analyzed by descriptive statistics, Chi-square test and SPSS software. Results: The lifestyle scores in five cases (8.33%) were undesirable, in 47 cases (78.33%) were relatively desirable, and eight cases (13.34%) had a desirable level of lifestyle. The chip-square test showed there was not significant relationship between the lifestyle and the elapsed time of cancer diagnosis, age, job, estrogen & progesterone receptor and menopause on subjects. (P>0.05) The relationship between lifestyle and education level, marital status, HER-2 oncogenes were significant (P<0.05). The average scores of physical activity and stress were lower than average level but average scores of feeding and opioid consumption were higher than the average level. Conclusion: Although our study results showed better lifestyle scores than previous studies, but they were significantly lower than ideal levels. With proper counseling and interventions (e.g. teaching relaxation techniques, appropriate physical activity, healthy diet, maintaining proper sleep patterns, and stress management) the lifestyle of patients can be promoted. Keywords: Cancer; Lifestyle; HER2-neu